RANCANGAN POSTER BIOLOGI SMA KELAS X PADA MATERI BAKTERI - Rosiana, Yuni; Zulfarina, Zulfarina; Darmawati, Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the potential of poster design in class X bacterial high school learning material. This research was conducted at the Binawidya Riau University in February-March 2020. This research was conducted in 2 stages: the experimental stage and the second stage is Poster Design that is analysis of the potential development of high school learning media Bacteria class X material. The study used an experimental method of descriptive qualitative research design. Based on the potential analysis, it was found that endophytic bacteria isolated from Laban plants can be used as a poster design of class X bacterial material for SMA 3.5 KD.Key Words: Poster, Bacteria